Extremist for Love : Martin Luther King Jr., Man of Ideas and Nonviolent Social Action - Burrow, Rufus, 1951- (Book collections on Project MUSE., 2014)
In spite of extensive research and publishing on King, insufficient attention has been given to the convergence of ideas and action in his life. In an era where people are often sorted into the categories of "thinker" and "doer," King stands out--a rare mix of the deeply profound thinker and intellect who put the fruit of that reflection into the service of direct social action.--Back cover.